2017
DOI: 10.1038/ncomms14892
|View full text |Cite
|
Sign up to set email alerts
|

Domain-dependent effects of insulin and IGF-1 receptors on signalling and gene expression

Abstract: Despite a high degree of homology, insulin receptor (IR) and IGF-1 receptor (IGF1R) mediate distinct cellular and physiological functions. Here, we demonstrate how domain differences between IR and IGF1R contribute to the distinct functions of these receptors using chimeric and site-mutated receptors. Receptors with the intracellular domain of IGF1R show increased activation of Shc and Gab-1 and more potent regulation of genes involved in proliferation, corresponding to their higher mitogenic activity. Convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
141
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(147 citation statements)
references
References 56 publications
6
141
0
Order By: Relevance
“…13,14 The 2 receptors consist of an extracellular a-subunit and a transmembrane b-subunit monomer. 15 Upon IGF-1 binding, the 2 receptors are auto-phosphorylated and insulin receptor substrates 1 and 2 (IRS-1 and IRS-2) are recruited, resulting in the activation of the 2 most prominent downstream signaling pathways, the phosphoinositide 3-kinase (PI3K)-Akt pathway and the MEK-extracellular signal-regulated kinase 1/2 (ERK1/2) pathway. 16,17 PI3K-AKT has been reported to enhance protein synthesis and cellular metabolism via mammalian target of rapamycin (mTOR) and to increase survival via p53, NF-kB, BAD/Bcl2, and FOXOs, whereas MEK-ERK1/2 activation mainly leads to increased cellular expansion.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The 2 receptors consist of an extracellular a-subunit and a transmembrane b-subunit monomer. 15 Upon IGF-1 binding, the 2 receptors are auto-phosphorylated and insulin receptor substrates 1 and 2 (IRS-1 and IRS-2) are recruited, resulting in the activation of the 2 most prominent downstream signaling pathways, the phosphoinositide 3-kinase (PI3K)-Akt pathway and the MEK-extracellular signal-regulated kinase 1/2 (ERK1/2) pathway. 16,17 PI3K-AKT has been reported to enhance protein synthesis and cellular metabolism via mammalian target of rapamycin (mTOR) and to increase survival via p53, NF-kB, BAD/Bcl2, and FOXOs, whereas MEK-ERK1/2 activation mainly leads to increased cellular expansion.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic effects of insulin, such as glucose uptake and lipid synthesis, are mainly regulated by the PI3K/AKT pathway 3 . By contrast, the MAPK pathway is the primary mediator of mitogenic effects of insulin, although the PI3K/AKT pathway is also involved 4,5 .…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Nowadays, growing studies suggested that IGF-1 participates in the modulation of a variety of physiological activities, including in cellular development, differentiation and proliferation [20] . For its positive role in improving muscle growth, association between IGF-1 polymorphisms and growth traits in livestock was extensively studied.…”
Section: Discussionmentioning
confidence: 99%